KEBUDAYAAN BEGAWI CAKAK PEPADUN DI TULANG BAWANG BARAT DALAM PERSPEKTIF POSKOLONIALISME - Shelvia Putri; Nova Lisna; Rahmat Prayogi (Jurnal Manajemen Pendidikan, 2025)
Culture is a representation that reflects the character and identity of a community. One of the traditions that continues to exist amid the strong influence of modernization is Begawi Cakak Pepadun, a customary ceremony distinctive to the Lampung Pepadun people, particularly in the Tulang Bawang Barat region. This tradition is not merely a ritual to inaugurate a penyimbang (traditional leader) or to bestow an honorary title, but it also embodies noble values such as mutual cooperation (sakai sambaian), Piil Pesenggiri (dignity and honor), and social responsibility toward the community. This study aims to (1) describe the implementation of the Begawi Cakak Pepadun tradition in Tulang Bawang Barat, and (2) analyze this cultural practice from a postcolonial perspective to understand how indigenous communities preserve their traditions amid colonial legacies, modernization, and globalization. The findings reveal that the implementation of Begawi consists of several main stages, namely preparation, manjau and ngedio, cangget (celebratory night), turun mandei, and cakak pepadun. Each stage holds symbolic meanings that represent togetherness and respect for ancestors. From a postcolonial perspective, Begawi Cakak Pepadun can be seen as a form of cultural resistance against colonial influence and as a process of reclaiming local identity. Although modernization has introduced changes such as the use of technology and adjustments in the duration of the ceremony, the Lampung people continue to preserve the spiritual and social essence of the tradition through mutual cooperation, cultural education for the younger generation, and the strengthening of customary institutions. Thus, Begawi is not merely a relic of the past but also a symbol of cultural continuity and resistance against global domination.